2003
DOI: 10.1037/0022-3514.85.5.909
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Structure for Repetitive Thought: What's on Your Mind, and How, and How Much?

Abstract: Although repetitive thought (RT) styles such as worry, rumination, and processing correlate positively, they have divergent effects on well-being, suggesting important dimensional variation. In Study 1, multidimensional scaling identified 2 dimensions--positive versus negative content valence and searching versus solving purpose--among students (N=978) who completed standard RT measures. In Study 2, students (N=100) sorted 25 descriptions of RT. Multidimensional scaling identified 4 dimensions, including valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
356
2
16

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(382 citation statements)
references
References 84 publications
8
356
2
16
Order By: Relevance
“…These findings are further supported by the results of prior studies conducted separately on worry and rumination. For example, Segerstrom, Stanton, Alden, & Shortridge (2003) found that negative affectivity is generated by negative thinking of any type; Chelminski & Zimmerman (2003) found that worry occurs in depression; and Nolen-Hoeksema (2000) found that rumination predicts the onset of anxiety. These findings suggest a shared component to these forms of repetitive thinking and a considerable research base supports this showing that anxiety and depression are frequently comorbid (Brown & Barlow, 1992;Brown, Campbell, Lehman, Grisham, & Mancill, 2001;Kessler et al, 1994;Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995;Kessler et al, 1998).…”
Section: The Link Between Rumination and Worrymentioning
confidence: 99%
“…These findings are further supported by the results of prior studies conducted separately on worry and rumination. For example, Segerstrom, Stanton, Alden, & Shortridge (2003) found that negative affectivity is generated by negative thinking of any type; Chelminski & Zimmerman (2003) found that worry occurs in depression; and Nolen-Hoeksema (2000) found that rumination predicts the onset of anxiety. These findings suggest a shared component to these forms of repetitive thinking and a considerable research base supports this showing that anxiety and depression are frequently comorbid (Brown & Barlow, 1992;Brown, Campbell, Lehman, Grisham, & Mancill, 2001;Kessler et al, 1994;Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995;Kessler et al, 1998).…”
Section: The Link Between Rumination and Worrymentioning
confidence: 99%
“…If ideation is a form of repetitive thinking that is linguistic (see Segerstrom, Stanton, Alden, & Shortridge, 2003), like rumination, a tendency to ruminate in the form of brooding on one's negative mood might increase vulnerability to having thoughts about suicide. In addition, past research suggests that rumination is characterized by an inflexible and perseverative cognitive style (Davis & Nolen-Hoeksema, 2000;Watkins & Brown, 2002) that can interfere with effective problem-solving (Lyubomirsky & Nolen-Hoeksema, 1995;Watkins & Baracaia, 2002) and mood regulation, deficits which are known to be associated with suicidality (e.g., Howat & Davidson, 2002;Williams, Barnhofer, Crane, & Beck, 2005;Zlotnick, Donaldson, Spirito, & Pearlstein, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Greenberg & Pyszczynski, 1986;Robinson & Alloy, 2003). Depressed and neurotic individuals, as well as those displaying generalized, social, and test anxiety, score higher on measures of self-consciousness and self-focused attention (see Ingram, 1990;Musson & Alloy, 1988;Pyszczynski & Greenberg, 1987, for reviews), suggesting that high levels of thinking about the self are symptomatic of psychological disorder, not psychological health (for work on adaptive forms of self-focusing, see Segerstrom, Stanton, Alden, & Shortridge, 2003;Trapnell & Campbell, 1999).…”
Section: What's So Bad About Dwelling?mentioning
confidence: 99%